L.A. Rebellion : creating a new black cinema - Stewart, Jacqueline Najuma, 1970-; Horak, Jan-Christopher; Field, Allyson Nadia, 1976- (University of California Press, 2015)
"L.A. Rebellion: Creating a New Black Cinema is the first book dedicated to the films and filmmakers of the L.A. Rebellion, a group of African and African American independent film and video artists that formed at the University of California, Los Angeles, in the 1970s and 1980s. The group--including Charles Burnett, Julie Dash, Haile Gerima, Billy Woodberry, Jamaa Fanaka, and Zeinabu irene Davis--shared a desire to create alternatives to the dominant modes of narrative, style, and practice in American cinema, works that reflected the full complexity of Black experiences. This landmark collection of essays and oral histories examines the creative output of the L.A. Rebellion, contextualizing the group's film practices and offering sustained analyses of the wide range of works, with particular attention to newly discovered films and lesser-known filmmakers. Based on extensive archival work and preservation, this collection includes a complete filmography of the movement, over 100 illustrations (most of which are previously unpublished), and a bibliography of primary and secondary materials. This is an indispensible sourcebook for scholars and enthusiasts, establishing the key role played by the L.A. Rebellion within the histories of cinema, Black visual culture, and postwar art in Los Angeles"--Provided by publisher.